Medieval period, book 1. - Byrne, Robert; Milliken Publishing Company (1971)
Focuses on Ireland, the Carolingians, the Vikings, the feudal system, and other aspects of medieval life in Europe.
With teacher's guide and duplicating masters.
Keywords: Middle Ages -- History; World history -- Medieval Period .; Europe -- History -- 476-1492.; Europe -- History -- 476-1492.; Middle Ages